2020
DOI: 10.3390/su12176729
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Preconceptions about Chicken and Pork Meat: A Qualitative Exploratory Study of Argentine Consumers in the Metropolitan Area of Buenos Aires

Abstract: In the past, the Argentine livestock production system was based on the extensive breeding that used pastures. However, technological progress and the use of land for soybean production are leading to a strong intensification of beef production, with a negative impact on the environment. According to FAO data, Argentina has the third highest meat consumption in the world, half of which is beef. A change in diet is a long and difficult process. The first step in favor of the environment could be the replacement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The narrow span of participants’ ages (two years) was purposed to focus on the relatively same level of Gen-Z consumers who were active in various activities (academic and social) and is up to date with trends including popular beverages. The sample size is considered sufficient to meet the research objective and for qualitative research in general and large enough to provide worthwhile evidence about behavioral patterns (Damico et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The narrow span of participants’ ages (two years) was purposed to focus on the relatively same level of Gen-Z consumers who were active in various activities (academic and social) and is up to date with trends including popular beverages. The sample size is considered sufficient to meet the research objective and for qualitative research in general and large enough to provide worthwhile evidence about behavioral patterns (Damico et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In other words, consumers will deal with positive or negative evaluations toward attributes that will drive their intention or motivation to buy (Schiffman and Wisenblit, 2015). This background has encouraged many scholars to investigate the typical attributes that motivate consumers to consume certain products (Damico et al , 2020; Neale et al , 2015). Motivation is defined as a driving force that impels an individual to act (Schiffman and Wisenblit, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…AAT has been used as a foundation of explanation in many studies, such as investigating bubble tea buying (Istijanto and Handoko, 2021), chicken and pork consumption (Damico et al , 2020), among others. These studies effectually found the positive (approach) and negative (avoidance) attributes that drive or inhibit people in a certain behavior, such as buying or consuming.…”
Section: Literature Reviewmentioning
confidence: 99%
“…That there are changes in habits in the adult population is a complicated problem which is exemplified in the dietary habits of people. Introducing edible insects or insect-based foods can be complex for the human paradigm (for ethical, religious, social, cultural, and psychological reasons) [ 13 ]. A first step to reduce the environmental footprint that indirectly generates the consumption of traditional animal-based foods may be to substitute plant-based feeds with insect-based foods.…”
Section: Introductionmentioning
confidence: 99%
“…These can have the same nutritional characteristics as conventional animal feed, but at the time of their development and production, they will generate a lower impact on the environment. This will also introduce the idea among consumers that insects can be a viable alternative to replace animal-based food [ 13 ].…”
Section: Introductionmentioning
confidence: 99%